Antioxidant activity of 1.3-bis(p-hydroxyphenyl)urea by CUPRAC and FRAP methods - Satria, Denny; Syukur Berkat Waruwu; Urip Harahap; Hari Purnomo4; Rifda Amaliya Ma’ruf (Talenta Publisher, 2023)
An imbalance in the number of free radicals produced in the body can result in oxidative stress. Excessive oxidative stress can lead to chronic inflammation, which in turn can lead to most chronic diseases. Inflammation is related to oxidation through increased reactive oxidative stress, which can target modulators associated with inflammation, such as inflammatory cytokines. Antioxidants can inhibit or stop oxidation by protecting the body and neutralizing free radicals. 1.3-bis(p-hydroxyphenyl)urea is a modification of p-aminophenol and has hepatotoxic side effects such as those caused by acetaminophen. This compound can relieve pain, is anti-inflammatory, and has fewer side effects. This research was conducted to evaluate the antioxidant activity of 1.3-bis(p-hydroxyphenyl)urea using the CUPRAC (Cupric Ion Reducing Antioxidant Capacity) method and the FRAP (Ferric Reducing Antioxidant Power) method. The results of the CUPRAC method research show that the 1.3-bis(p-hydroxyphenyl)urea compound has an IC50 value of 4.40 ± 0.07 μg/mL. Meanwhile, the FRAP method was 29.36 ± 1.20 μg/mL. Apart from suppressing inflammation, this compound has the potential to be an antioxidant compound.